Modal response of hybrid raster orientation on material extrusion printed acrylonitrile butadiene styrene and polyethylene terephthalate glycol under thermo-mechanical loads - Almutairi, Mohammed Dukhi; Mascarenhas, Taheer A.; Alnahdi, Sultan Saleh; He, Feiyang; Khan, Muhammad A. (Elsevier, 2023)
In this paper we look at Acrylonitrile Butadiene Styrene (ABS) and Polyethylene Terephthalate Glycol (PETG), chosen for their low cost, high strength and temperature resistance. This study evaluates the bending fatigue performance of Material extrusion (MEX) ABS and PETG cantilever beams and compares their properties while varying a printing parameter under thermal loads. The study, using custom building orientation angles of 90o, 45o and 60o between the layers, tested the beams at different temperatures from 30o to 50 °C. The results show the effects of the building orientations and the effects of temperature on the sample. The printing orientation, which is the same as loading, also slows the crack growth.
Keywords: Hybrid raster orientation; ABS; PETG; Fatigue bending test; Variable ambient temperature